An apple a day won't keep the doctor away: presentation, treatment, and outcome in pediatric apple aspirations. Issue 7 (22nd May 2020) - Zychlinsky Scharff, Anna; Schwerk, Nicolaus; Baumann, Ulrich; Burmester, Helen; Carlens, Julia; Dopfer, Christian; Grewendorf, Simon; Mueller, Carsten; Schütz, Katharina; Voelker, Marc; Hansen, Gesine; Happle, Christine; et al.
Abstract: Introduction: Foreign body (FB) aspiration is a frequent and preventable source of morbidity and mortality, especially in children under 4 years of age. Few comprehensive studies exist on presentation and outcome of apple aspirations in children. Methods: In a retrospective analysis of bronchoscopy records of a tertiary medical care center from January 2007 to August 2019, we identified pediatric cases of suspected apple aspirations. Results: A total of 11 suspected apple aspirations were identified (observation time 12.7 years, n = 5858 bronchoscopies, n = 226 interventions due to suspected FB aspirations in total). The mean age of patients was 24 months (standard error mean, 7 months; range, 8‐83 months), and 6 out of 11 cases (55%) were male. Bronchoscopy confirmed apple aspiration in n = 6/11 cases (55%). In n = 2/11 cases (18%), a bite of the apple was located in the esophagus causing significant tracheal narrowing, and in n = 3/11 cases (27%), no FB was found. In all cases of airway FB identification, extraction was successful. Hypersalivation was associated with esophageal FB location, whereas persistent cough, stridor, or dyspnea were associated with airway FB location. Outcomes ranged from complete reconstitution 1 day after bronchoscopy in most cases to hypoxemia with severe brain damage in one patient. Discussion: This analysis shows that apple aspirations are not entirely uncommon in children and may lead to disastrous complications. Typical signs of airway location are persistent cough, stridor or dyspnea, whereas hypersalivation may point toward an esophageal location. In each case of suspected apple aspiration, timely bronchoscopy with possible FB extraction should be performed by an experienced team.